Retrospective cross sectional analysis of an acupuncture intervention for chronic pain management at Groote Schuur Hospital Pain Clinic Cape Town, South Africa - Lagerstrom, Nada (Department of Psychiatry and Mental Health, 2020)
In 2015 acupuncture was introduced as an alternative intervention in the management of chronic pain, at the Chronic Pain Management Clinic of Groote Schuur Hospital, a tertiary academic hospital in Cape Town, South Africa. This study is a retrospective, cross-sectional analysis that aimed to investigate several aspects of the acupuncture intervention over a 12 month period. The main outcome measure, the Brief Pain Inventory (BPI), is a widely used, internationally validated questionnaire, containing pain intensity, pain interference, and total score. The main objective of this study was to determine if the acupuncture treatment lowered BPI scores after 6 to 9 intervention sessions. Additional objectives were to determine if there are any correlations between demographic and clinical factors and changes in BPI scores, and to describe the demographic and clinical characteristics of the study population. The data was obtained by folder reviews of 66 patients with chronic pain who were referred for acupuncture treatment between January 1, 2015 and December 31, 2015, and attended at least one treatment session. The full treatment course (6-9 sessions) was completed by 24 patients (36,3%), with an average post treatment decrease in BPI of 3,7 points. Responders (patients who obtained 2 and more point BPI decrease) comprised 70,6% of the patients who completed treatment. Decrease in BPI scores after completion of full acupuncture treatment proved to be statistically significant (p=0.002). Factors showing strongest correlation with BPI decrease were female gender and absence of medical and psychiatric co-morbidities.